Cell-cycle regulation of NOTCH signaling during C. elegans vulval development - Nusser-Stein, Stefanie (European Molecular Biology Organization, 2012)
C. elegans vulval development is one of the best-characterized systems to study cell fate specification during organogenesis. The detailed knowledge of the signaling pathways determining vulval precursor cell (VPC) fates permitted us to create a computational model based on the antagonistic interactions between the epidermal growth factor receptor (EGFR)/RAS/MAPK and the NOTCH pathways that specify the primary and secondary fates, respectively. A key notion of our model is called bounded asynchrony, which predicts that a limited degree of asynchrony in the progression of the VPCs is necessary to break their equivalence. While searching for a molecular mechanism underlying bounded asynchrony, we discovered that the termination of NOTCH signaling is tightly linked to cell-cycle progression. When single VPCs were arrested in the G1 phase, intracellular NOTCH failed to be degraded, resulting in a mixed primary/secondary cell fate. Moreover, the G1 cyclins CYD-1 and CYE-1 stabilize NOTCH, while the G2 cyclin CYB-3 promotes NOTCH degradation. Our findings reveal a synchronization mechanism that coordinates NOTCH signaling with cell-cycle progression and thus permits the formation of a stable cell fate pattern.